Polyamines – A New Metabolic Switch: Crosstalk With Networks Involving Senescence, Crop Improvement, and Mammalian Cancer Therapy - Sobieszczuk-Nowicka, Ewa; Paluch-Lubawa, Ewelina; Mattoo, Autar K.; Arasimowicz-Jelonek, Magdalena; Gregersen, Per L.; Pacak, Andrzej (Frontiers in Plant Science, 2019)
Polyamines (PAs) are low molecular weight organic cations comprising biogenic amines that play multiple roles in plant growth and senescence. PA metabolism was found to play a central role in metabolic and genetic reprogramming during dark-induced barley leaf senescence (DILS). Robust PA catabolism can impact the rate of senescence progression in plants. We opine that deciphering senescence-dependent polyamine-mediated multidirectional metabolic crosstalks is important to understand regulation and involvement of PAs in plant death and re-mobilization of nutrients during senescence. This will involve optimizing the use of PA biosynthesis inhibitors, robust transgenic approaches to modulate PA biosynthetic and catabolic genes, and developing novel germplasm enriched in pro- and anti-senescence traits to ensure sustained crop productivity. PA-mediated delay of senescence can extend the photosynthesis capacity, thereby increasing grain starch content in malting grains such as barley. On the other hand, accelerating the onset of senescence can lead to increases in mineral and nitrogen content in grains for animal feed. Unraveling the “polyamine metabolic switch” and delineating the roles of PAs in senescence should further our knowledge about autophagy mechanisms involved in plant senescence as well as mammalian systems. It is noteworthy that inhibitors of PA biosynthesis block cell viability in animal model systems (cell tumor lines) to control some cancers, in this instance, proliferative cancer cells were led toward cell death. Likewise, PA conjugates work as signal carriers for slow release of regulatory molecule nitric oxide in the targeted cells. Taken together, these and other outcomes provide examples for developing novel therapeutics for human health wellness as well as developing plant resistance/tolerance to stress stimuli.